Fluacrypyrim Protects Hematopoietic Stem and Progenitor Cells against Irradiation via Apoptosis Prevention - Xuewen Zhang; Zizhi Qiao; Bo Guan; Fangming Wang; Xing Shen; Hui Shu; Yajun Shan; Yuwen Cong; Shuang Xing; Zuyin Yu (Molecules, 2024)
Ionizing radiation (IR)-induced hematopoietic injury has become a global concern in the past decade. The underlying cause of this condition is a compromised hematopoietic reserve, and this kind of hematopoietic injury could result in infection or bleeding, in addition to lethal mishaps. Therefore, developing an effective treatment for this condition is imperative. Fluacrypyrim (FAPM) is a recognized effective inhibitor of STAT3, which exhibits anti-inflammation and anti-tumor effects in hematopoietic disorders. In this context, the present study aimed to determine whether FAPM could serve as a curative agent in hematopoietic-acute radiation syndrome (H-ARS) after total body irradiation (TBI). The results revealed that the peritoneally injection of FAPM could effectively promote mice survival after lethal dose irradiation. In addition, promising recovery of peripheral blood, bone marrow (BM) cell counts, hematopoietic stem cell (HSC) cellularity, BM colony-forming ability, and HSC reconstituting ability upon FAPM treatment after sublethal dose irradiation was noted. Furthermore, FAPM could reduce IR-induced apoptosis in hematopoietic stem and progenitor cells (HSPCs) both in vitro and in vivo. Specifically, FAPM could downregulate the expressions of p53-PUMA pathway target genes, such as Puma, Bax, and Noxa. These results suggested that FAPM played a protective role in IR-induced hematopoietic damage and that the possible underlying mechanism was the modulation of apoptotic activities in HSCs.